The Effect Of Price Perception And Personal Selling On Car Purchase Decisions At PTArista Jaya Lestari – Wuling Jayakarta - Marison Sitorus; Calista Syahla (Jurnal Teknologi dan Manajemen, 2022)
This research aims to determine the effect of price perception and personal selling both partially and simultaneously on Car Purchase Decision at PT Arista Jaya Lestari – Wuling Jayakarta. This study uses the independent variables price perception (X1) and personal selling (X2) as well as the dependent variable purchasing decisions (Y). This analysis uses quantitative methods using probability sampling with simple random sampling techniques. The analytical method used is multiple linear regression analysis. The data obtained is the result of primary data from distributed questionnaires and interviews and secondary data obtained from companies, books, previous journals, and articles. The sample used to fill out the questionnaire using a likert scale in this study was 83 respondents who are consumers who have made purchases Wuling car at PT Arista Jaya Lestari - Wuling Jayakarta. The data analysis used was validity and reliability test, classical assumption test, coefficient of correlation and determination test, linear multiple regression analysis, and hypothesis testing. The study's conclusion shows that price perception and personal selling simultaneously and partially have a positive and significant effect on Car Purchase Decisions at PT Arista Jaya Lestari – Wuling Jayakarta.